The complete mitochondrial genome of Lutjanus ophuysenii and phylogenetic analysis. Issue 8 (3rd August 2021) - Sun, Peng; Jiang, Yazhou; Yuan, Xingwei; Zhang, Hui
Abstract: The complete mitochondrial genome of Lutjanus ophuysenii was analyzed by the next-generation sequencing. It was composed of 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNA), 2 ribosomal RNA genes (rRNA), and a control region with a total length of 16, 498 bp. This mitochondrial genome has a base composition of 27.78% A, 16.55% G, 30.68% C, and 24.98% T. The phylogenetic analysis revealed that the L. ophuysenii has the closest relationship with L. votta . This mitochondrial genome provides important information for the phylogenetic relationship and genetic resource in this species.